Long‐term administration of rifaximin improves the prognosis of patients with decompensated alcoholic cirrhosis. Issue 3 (26th February 2013) - Vlachogiannakos, Jiannis; Viazis, Nikos; Vasianopoulou, Panagiota; Vafiadis, Irene; Karamanolis, Dimitrios G; Ladas, Spiros D
Abstract Background and Aim Cirrhotic patients are predisposed to intestinal bacterial overgrowth with translocation of bacterial products which may deteriorate liver hemodynamics. Having shown that short‐term administration of rifaximin improves liver hemodynamics in decompensated cirrhosis, we conducted this study to investigate the effect of intestinal decontamination with rifaximin on the long‐term prognosis of patients with alcohol‐related decompensated cirrhosis (Child‐Pugh > 7) and ascites. Methods Patients who had received rifaximin and showed improved liver hemodynamics were enrolled in the current study and continued to receive rifaximin (1200 mg/day). Each patient was matched by age, sex, and Child‐Pugh grade to two controls and followed up for up to 5 years, death or liver transplantation. Survival and risk of developing portal hypertension‐related complications were compared between rifaximin group and controls. Results Twenty three patients fulfilled the inclusion criteria and matched with 46 controls. Patients who received rifaximin had a significant lower risk of developing variceal bleeding (35% vs 59.5%, P = 0.011), hepatic encephalopathy (31.5% vs 47%, P = 0.034), spontaneous bacterial peritonitis (4.5% vs 46%, P = 0.027), and hepatorenal syndrome (4.5% vs 51%, P = 0.037) than controls. Five‐year cumulative probability of survival was significantly higher in patients receiving rifaximin than in controls (61% vs 13.5%, P = 0.012). In the multivariate analysis, rifaximin administration was independently associated with lower risk of developing variceal bleeding, hepatic encephalopathy, spontaneous bacterial peritonitis, hepatorenal syndrome, and higher survival. Conclusions In patients with alcohol‐related decompensated cirrhosis, long‐term rifaximin administration is associated with reduced risk of developing complications of portal hypertension and improved survival.